2020
DOI: 10.1016/j.immuni.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal SARS-CoV-2 Serological Assays Enable Surveillance of Low-Prevalence Communities and Reveal Durable Humoral Immunity

Abstract: We conducted a serological study to define correlates of immunity against SARS-CoV-2. Relative to mild COVID-19 cases, individuals with severe disease exhibited elevated virus-neutralizing titers and antibodies against nucleocapsid (N) and the receptor binding domain (RBD) of spike protein. Age and sex played lesser roles. All cases, including asymptomatic individuals, seroconverted by 2 weeks post-PCR confirmation. Spike RBD and S2 and neutralizing antibodies remained detectable through 5-7 months post-onset,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
307
3
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(385 citation statements)
references
References 69 publications
58
307
3
5
Order By: Relevance
“…Overall, the detection of SARS-CoV-2 Abs with commercial tests was higher despite important heterogeneity between the assays evaluated herein. In a previous study [3], about 40% of asymptomatic subjects became negative for IgG to the N protein within 3 to 6 months, which is consistent with that presented herein for the Architect assay. This suggests that assays detecting only antibodies against the N protein must not be used in long-term seroprevalence surveys.…”
supporting
confidence: 91%
“…Overall, the detection of SARS-CoV-2 Abs with commercial tests was higher despite important heterogeneity between the assays evaluated herein. In a previous study [3], about 40% of asymptomatic subjects became negative for IgG to the N protein within 3 to 6 months, which is consistent with that presented herein for the Architect assay. This suggests that assays detecting only antibodies against the N protein must not be used in long-term seroprevalence surveys.…”
supporting
confidence: 91%
“…Further evidence is required to evaluate comprehensively the apparent waning of the nAb response over time: in the studies included here although nAb may be detectable, higher quality studies suggest that titres are generally low, and the response is short lived. Although this is supported by recently published data (beyond the date cut off for inclusion in this study) from a UK cohort of healthcare professionals with follow up to three months [163], durable neutralising antibody response up to seven months have now been described [164]. Ongoing vaccine research has highlighted a need for evidence of longer-term protection due to nAbs, and the titres at which these effects are achieved-neither of which were fully addressed by studies included in this review.…”
Section: Summary Of Findingssupporting
confidence: 73%
“…It is not possible to draw robust conclusions on the associations of antibody response with age, sex, ethnicity or comorbidities, and although disease severity positively correlated with higher IgG antibody titres in a number of studies, distinguishing causation from correlation is not possible. More recent evidence shows that while responses may be of lower magnitude in milder cases, they are still elicited and may be protective-although evidence on response patterns in milder illness remains in short supply [164,169].…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…In contrast, data from some studies have indicated that neutralizing antibody titers remain stable ranging from 75 days to 6 months PSO in COVID-19 convalescent individuals with a broad spectrum of disease severity (130,134,141,142). In particular, a large cohort study by Wajnberg et al analyzed humoral responses in 30,032 antibody-positive individuals in New York City, and demonstrated relatively stable anti-S IgG antibody titers over five months, with these titers correlating with virus neutralization (130).…”
Section: Duration Of Sars-cov-2 Neutralizing Antibodiesmentioning
confidence: 98%